Impact of media on opinion dynamics of interacting networks - Ma, Hongxuan (Nanyang Technological University, 2020)
People’s opinions are formed by various social interactions. Individuals acquire information by communicating with their friends or read news from different types of media resources. To better understand this scenario, the opinion dynamics studies in the field of Social Network Analysis (SNA) investigate the behaviour of opinion models on different networks. In this research, we explore a multi-level interacting opinion dynamics model which includes networks for both normal individuals and official media agents. Varying the media network structure, the impact of media on individuals’ opinion dynamic process is observed. Although the overall individuals’ performances look similar, the in-behind mechanism caused by distinct media structures is different. Generally, for individuals who have little faith among their friends, with more openness towards the media, they firstly reach agreements but then split for dispersion. As for individuals who trust their friends, with more acceptance towards media agents, they evolve from initial consensus to disagreements.